2005
DOI: 10.1128/mcb.25.6.2138-2146.2005
|View full text |Cite
|
Sign up to set email alerts
|

Combined Global Localization Analysis and Transcriptome Data Identify Genes That Are Directly Coregulated by Adr1 and Cat8

Abstract: In Saccharomyces cerevisiae, glucose depletion causes a profound alteration in metabolism, mediated in part by global transcriptional changes. Many of the transcription factors that regulate these changes act combinatorially. We have analyzed combinatorial regulation by Adr1 and Cat8, two transcription factors that act during glucose depletion, by combining genome-wide expression and genome-wide binding data. We identified 32 genes that are directly activated by Adr1, 28 genes that are directly activated by Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
166
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(172 citation statements)
references
References 53 publications
6
166
0
Order By: Relevance
“…In particular, we explored the degree to which nucleosome occupancy over transcription factor binding motifs changed as a function of changes in expression or influenced their use in promoting transcriptional change. Genes regulated by the glucose-repressive transcription factors Adr1 and Cat8 (Tachibana et al, 2005) gain promoter nucleosomes during glucose repression (Verdone et al, 1996;Agricola et al, 2004). Consistent with these prior observations, we observed that many Adr1/Cat8-regulated genes gained promoter nucleosomes on transcriptional repression ( Figure 4A).…”
Section: Functional Transcription Factor Binding Motifs Reside In Regsupporting
confidence: 80%
“…In particular, we explored the degree to which nucleosome occupancy over transcription factor binding motifs changed as a function of changes in expression or influenced their use in promoting transcriptional change. Genes regulated by the glucose-repressive transcription factors Adr1 and Cat8 (Tachibana et al, 2005) gain promoter nucleosomes during glucose repression (Verdone et al, 1996;Agricola et al, 2004). Consistent with these prior observations, we observed that many Adr1/Cat8-regulated genes gained promoter nucleosomes on transcriptional repression ( Figure 4A).…”
Section: Functional Transcription Factor Binding Motifs Reside In Regsupporting
confidence: 80%
“…We focused on the NIR-predicted transcriptional regulation of SNF1 by Hxk2, Med8, and Mig1, and confirmed Hxk2 and Med8 as direct regulators and Mig1 as an indirect regulator of SNF1 expression in 2% glucose growth. Hxk2 and Med8 were also found to repress CAT8, a major activator of gluconeogenic genes (7,29). These results suggest a glucose-responsive signaling mechanism for Hxk2 worthy of further study, given the previously reported challenges in clarifying its downstream targets (9,24,27).…”
Section: Discussionmentioning
confidence: 87%
“…In vivo TF-promoter binding for the repressor Mig1 (10) and the gluconeogenic activators Cat8 (29) and Sip4 (10) has been observed by chromatin immunoprecipitation/DNA microarrays (ChIP-chip) and other experimental methods (see Table S1). Hxk2 and Med8 were previously identified with Mig1 as physical repressors of SUC2 expression (24,25), and Med8 as a repressor of HXK2, binding cis-regulatory sequences within its coding region (24).…”
Section: Experimental Verification Of Network Model Predictionsmentioning
confidence: 99%
“…The complex dynamics of gene expression during the cell cycle and after subjecting cells to stress have been assayed by ChIP analysis of the regulatory TFs and coactivators (McBride et al 1997;Bhoite et al 2001;Simon et al 2001;Horak et al 2002;Tan et al 2008;Ni et al 2009). Similarly, during sporulation (Kahana et al 2010) and glucose starvation (Young et al 2003;Tachibana et al 2005;Ratnakumar and Young 2010) multiple TFs bind upstream of the promoter of coregulated genes. In the sulfur metabolic network, the non-DNA-binding Met4 activator interacts with multiple cofactors that stabilize DNA binding (Lee et al 2010).…”
Section: Uas Function and Combinatorial Controlmentioning
confidence: 99%